ALIH KODE DAN CAMPUR KODE DALAM PERCAKAPAN WHATSAPP GRUPSTAF LABORATORIUM FAKULTAS TARBIYAH DAN ILMU KEGURUANUNIVERSITAS ISLAM NEGERI PROF. K. H. SAIFUDDIN ZUHRI PURWOKERTO - Malia Fransisca; Syaifullah (Fakultas Syariah dan Adab Universitas Nahdlatul Ulama Sunan Giri, 2022)
Code-Switching and Code-Mixing often occur in conversations of twoor more languages. This triggered researchers to examine the conversationscontained in WhatsApp Groups. The purpose of this study was to determine thecode switching and code mixing that occurred between Indonesian, Javanese andNgapak Banyumasan languages. The research method used is a qualitativemethod. The author breaks down the conversation in WAG based on its smallestelements. The result of this research is the existence of code switching andinternal and external code mixing in the conversation. This means that the codeswitching and code mixing that occurred was between Indonesian to Javanese,ordinary Javanese to Ngapak, Indonesian to Ngapak, ordinary Javanese toNgapak or Indonesian to English.